2007
DOI: 10.1016/j.ccr.2007.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Tumor Cell Adhesion Promotes Angiogenic Switch and Progression to Micrometastasis in RAF-Driven Murine Lung Cancer

Abstract: Progression of non-small-cell lung cancer (NSCLC) to metastasis is poorly understood. Two genetic approaches were used to evaluate the role of adherens junctions in a C-RAF driven mouse model for NSCLC: conditional ablation of the cdh1 gene and expression of dominant-negative (dn) E-cadherin. Disruption of E-cadherin caused massive formation of intratumoral vessels that was reversible in the early phase of induction. Vascularized tumors grew more rapidly, developed invasive fronts, and gave rise to micrometast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 40 publications
3
61
1
Order By: Relevance
“…Immunofluorescence analysis revealed increased E-cadherin expression after siRNA-CHRNA5 treatment. Previous data show that membrane loss of E-cadherin leads to cell-cell separation and promotes the angiogenic switch in lung cancer (Ceteci et al, 2007). These suggested that a5-nAChR might play an important role in nicotine-induced migration and invasion of A549 cells.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Immunofluorescence analysis revealed increased E-cadherin expression after siRNA-CHRNA5 treatment. Previous data show that membrane loss of E-cadherin leads to cell-cell separation and promotes the angiogenic switch in lung cancer (Ceteci et al, 2007). These suggested that a5-nAChR might play an important role in nicotine-induced migration and invasion of A549 cells.…”
Section: Discussionmentioning
confidence: 94%
“…Knockdown of a5-nAChR enhanced E-cadherin expression E-cadherin, a gene expressed in most normal epithelial tissues. Its loss in several carcinomas leads to increased tumor invasiveness, angiogenesis and epithelial to mesenchymal transition (EMT) (Ceteci et al, 2007;Ishiyama et al, 2010). Therefore, we investigated the role of a5-nAChR in lung cancer by analyzing E-cadherin associated with cell adhesion and migration.…”
Section: The Effects Of Nicotine On the Expression Of A5-nachrmentioning
confidence: 99%
“…Tumor angiogenesis, the new generation or modulation of tumor vessels, has been recognized as a hallmark step during carcinogenesis, promoting tumor metastasis (31)(32)(33). In view of this, vascularized human tumors such as non-small-cell lung cancer have been found to metastasize early in carcinogenesis to regional lymph nodes, correlating with the degree of lymphangiogenesis Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, multiple independent groups have established a causal role for E-cadherin dysfunction or loss in tumor development and progression (Perl et al, 1998;Derksen et al, 2006;Ceteci et al, 2007). It is well recognized that inactivation of E-cadherin leads to cytosolic translocation of p120 in colon, breast, bladder, lung, pancreas, prostate and stomach tumors, which has been associated with tumor malignancy (reviewed by Thoreson and Reynolds, 2002).…”
Section: Roles For P120 In Cancermentioning
confidence: 98%